2016
DOI: 10.1002/term.2240
|View full text |Cite
|
Sign up to set email alerts
|

Proprotein convertase inhibition promotes ciliated cell differentiation - a potential mechanism for the inhibition of Notch1 signalling by decanoyl-RVKR-chloromethylketone

Abstract: Chronic repetitive rounds of injury and repair in the airway lead to airway remodelling, including ciliated cell loss and mucous cell hyperplasia. Airway remodelling is mediated by many growth and differentiation factors including Notch1, which are proteolytically processed by proprotein convertases (PCs). The present study evaluated a novel approach for controlling basal cell‐type determination based on the inhibition of PCs. It was found that decanoyl‐RVKR‐chloromethylketone (CMK), a PC inhibitor, promotes c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The mechanism for leptin elevating POMC-derived peptide concentrations could be due to its previously observed effects on inducing POMC transcription and translation [26] , [28] , its effects on promoting prohormone processing by increasing PC1/3 and PC2 expression [29] , or some combination of the two. Conversely, treatment of cultures with a broad-spectrum PC inhibitor that is likely to inhibit many PC enzymes at the concentration used [90] , [91] significantly reduced concentrations of POMC-derived peptides. Together, these findings are consistent with observations made in animals, suggesting that this human cellular model system may have predictive power for understanding human-specific aspects of POMC biology, such as the regulation of β-MSH processing and secretion.…”
Section: Discussionmentioning
confidence: 97%
“…The mechanism for leptin elevating POMC-derived peptide concentrations could be due to its previously observed effects on inducing POMC transcription and translation [26] , [28] , its effects on promoting prohormone processing by increasing PC1/3 and PC2 expression [29] , or some combination of the two. Conversely, treatment of cultures with a broad-spectrum PC inhibitor that is likely to inhibit many PC enzymes at the concentration used [90] , [91] significantly reduced concentrations of POMC-derived peptides. Together, these findings are consistent with observations made in animals, suggesting that this human cellular model system may have predictive power for understanding human-specific aspects of POMC biology, such as the regulation of β-MSH processing and secretion.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, this hypothesis was tested in a study using a broad-spectrum inhibitor of furin, decanoyl-RVKR-CMK, which demonstrated that treatment of human nasal epithelial cells with this inhibitor showed reduced Notch1 processing and enhanced ciliated cell differentiation. Knockdown of furin in these cells also caused a reduction in Notch1 processing and an increase in ciliated cell numbers, further demonstrating the involvement of furin in this process [ 83 ].…”
Section: Other Key Roles For Furin In Cf Airways Disease Pathogenesismentioning
confidence: 99%
“…CRISPR/Cas9 mediated depletion of FoxJ1 and subsequent multi-parametric analysis of HBEC ALI models, showed significant reduction of mucociliary differentiation into the ciliated cell phenotype without affecting barrier integrity (Rapiteanu et al, 2020). Efficacy testing of novel compounds, such as proprotein convertase inhibitors, acting via Notchdependant mechanisms have been shown to promote ciliagenesis in the 3D ALI models (Lee et al, 2017).…”
Section: Mucociliary Differentiation Of Basal Progenitor Cells Into M...mentioning
confidence: 99%